Differential Status Evaluations and Racial Bias in the Chilean Segregated School System1. Issue 2 (22nd March 2018) - Salgado, Mauricio; Castillo, Javier
Abstract : Although there is growing interest in studying the long‐ignored relationship between stratification and race in Chile, racial bias in person perception remains unknown. We hypothesize that the segregation of the Chilean school system generated a prestige order in which pupils are differentiated by status characteristics according to the type of school they attend, and that these evaluations are based on racial traits. To test this hypothesis, we study whether facial appearance is sufficient to impute the type of school a pupil is attending, and whether these categorizations evoke different status evaluations of wealth and morality based on race. Results confirm that participants' perceptions of facial appearance allow them to situate pupils in the Chilean social structure. Faces categorized as studying at different types of schools varied in their perceived wealth. However, the relationship between moral traits and types of schools was weak. We also found evidence of racial bias in the participants' perceptions of pupils' faces: faces categorized as enrolled in municipal schools (low status) were judged with Amerindian or mestizo racial traits, while faces categorized as attending private fee‐paying schools (high status) were judged with white racial traits. We did not find a relationship between race and morality.